An inter-institutional development experience in a MOOCs for in-service teachers - María Guadalupe Tinajero Villavicencio; Jaqueline Mata Santel; Karla Monserratt Villaseñor Palma; Alma Cecilia Carrasco Altamirano (Universidad de Guadalajara, 2019)
This article presents some of the conceptual and methodological aspects concerning the design of a MOOC for in-service primary school teachers. Upon receiving the Codaes-Descaes support, researchers and students from three public universities established a development program based on phases, which basically consisted in articulating a design approach, a anagement model and an organizational structure. The focus centers on the management strategy used to merge intra and interinstitutional work from specialists from different fields of knowledge. We also present the MOOC contents on Initial Literacy, and discuss the importance of summing up efforts to develop digital learning resources and maximizing the Open Educational Resources according to the affordances of the platform that will host the MOOC.